Improving Network Performance Using An Intrusion Detection & Adaptive Response Approach For Manets (International Journal of Engineering and Computer Science, 2017)
A mobile ad hoc network (MANET) is normally a, infrastructure-less network of mobile devices connected without wires. But protecting the network layer from malicious attacks is an important and challenging security issue in mobile ad hoc networks (MANETs). Mobile ad hoc networks are vulnerable to a variety of network layer attacks such as black hole, gray hole, sleep deprivation & rushing attacks. Intrusion detection and prevention provides a way to protect mobile ad hoc networks (MANETs) from attacks by external or internal intruders. So, in the existing system cost sensitive model for Intrusion Response Systems (IRS) is used in fixed networks. This technique relies on comparing the cost of deploying a response against the cost of damage caused by an “un-attended” intrusion and decides to preemptively deploy a response with maximum benefit. But the problem is In MANETs it is difficult to calculate the intrusion response cost, which we can define as the negative impact on the network resources caused by the response. So, in the proposed system an intrusion detection & adaptive response mechanism (IDAR) for MANETs is presented that detects a range of attacks and provides an effective response with low network degradation. The deficiencies of a fixed response to an intrusion are considered and we overcome these deficiencies with a flexible response scheme that depends on the measured confidence in the attack, the severity of attack and the degradation in network performance. We present results from an implementation of the response scheme that has three intrusion response actions. Simulation results show the effectiveness of the proposed detection and adaptive response mechanisms in various attack scenarios. An analysis of the impact of our proposed scheme shows that it allows a flexible approach to management of threats and demonstrates improved network performance with a low network overhead.